(untitled) (The Pakistan Development Review, 2000)
Information on wage levels is essential in evaluating the living standards and conditions of work and life of the workers. Since nominal wage fails to explain the purchasing power of employees, real wage is considered as a major indicator of employees purchasing power and can be used as proxy for their level of income. Any fluctuations in the real wage rate have a significant impact on poverty and the distribution of income. When used in relation with other economic variables, for instance employment or output they are valuable indicators in the analysis of business cycles. There has been a long debate regarding the relationship between real wages and the employment (output). Despite the apparent simplicity, the relationship between real wages and output has remained deceptive both theoretically and empirically. Keynes (1936) viewed cyclical movements in employment along a stable labour demand schedule thus indicating counter cyclical real wages. His deduction is in line with sticky wages and sticky expectations, which augments models like Phillips curve. In these models real wages behaved as counter-cyclical as nominal wages are slow to adjust during recession (decrease in aggregate demand and associated slowdown in price growth). Stickiness of wages or expectations shifts the labour supply over the business cycles [Abraham and Haltiwanger (1995)]. Barro (1990) and Christiano and Eichenbaum (1992) have associated these labour supply shifts with intertemporal labour-leisure substitution. This in response to temporary changes in real interest rates (fiscal policy shocks) could yield counter-cyclical real wages. However, Long and Plosser (1983) and Kydland and Prescott (1982) while studying the real business cycle models highlight on the technology shocks which leads to pro-cyclical real wages.